Secondary malignancy in a vulva cancer patient – HPV-induced field cancerization: A case report (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Human papillomavirus (HPV) infection is associated with oropharyngeal and anogenitalcancers in men and women. Approximately 90% of all cervical cancers are attributed to high-risk HPVinfections, and 60% of squamous cell carcinomas (SCC) of the vulva, vagina, anus, and penis are due toHPV infection.Case presentation: We present the case of a 26-year-old with retroviral disease managed for locallyadvanced vulva cancer on external beam radiotherapy followed by wide excision of the residual tumorand bilateral inguino femoral nodal dissection. She later presented with a history of foul-smelling vaginaldischarge. A biopsy confirmed moderately differentiated squamous cell carcinoma of the cervix clinicallyand radiologically staged at 2B and 3B, respectively. She was scheduled to start chemotherapy withcarboplatin and paclitaxel after blood transfusion due to anemia.Discussion: Field cancerization was coined by Slaughter et al. to describe the existence of generalizedcarcinogen-induced early genetic changes in the epithelium from which multiple independent lesionsoccur, leading to the development of multifocal tumors. In some cases, multiple contiguous tumor focicoalesce, hence the lateral spread of squamous cell cancers. It was also observed that normal-lookingcells near malignant cells were histologically abnormal and therefore were part of the transformed cells ina particular tumor field and consequently were responsible for the occurrence of local tumorrecurrences.Conclusion: Field cancerization is a well-known and well-documented process of malignanttransformation. Several studies have confirmed the importance of this phenomenon in tumordevelopment. Surveillance is the key to detecting early recurrence and secondary malignancies.